A Research‐inspired biochemistry laboratory module–combining expression, purification, crystallization, structure‐solving, and characterization of a flavodoxin‐like protein. Issue 3 (11th February 2019) - Hammerstad, Marta; Røhr, Åsmund K.; Hersleth, Hans‐Petter
Abstract: Many laboratory courses consist of short and seemingly unconnected individual laboratory exercises. To increase the course consistency, relevance, and student engagement, we have developed a research‐inspired and project‐based module, "From Gene to Structure and Function". This 2.5‐week full‐day biochemistry and structural biology module covers protein expression, purification, structure solving, and characterization. The module is centered around the flavodoxin‐like protein NrdI, involved in the activation of the bacterial ribonucleotide reductase enzyme system. Through an in‐depth focus on one specific protein, the students will learn the basic laboratory skills needed in order to generate a broader knowledge and breadth within the field. With respect to generic skills, the students report their findings as a scientific article, with the aim to learn to present concise research results and write scientific papers. The current research‐inspired project has the potential of being further developed into a more discovery‐driven project and extended to include other molecular biological techniques or biochemical/biophysical characterizations. In student evaluations, this research‐inspired laboratory course has received very high ratings and been highly appreciated, where the students have gained research experience for more independent future work in the laboratory. © 2019 The Authors. Biochemistry and Molecular Biology Education published by Wiley Periodicals, Inc. on behalf of International Union of Biochemistry and Molecular Biology, 47(3):318–332, 2019.